2019
DOI: 10.1186/s13395-019-0214-1
|View full text |Cite
|
Sign up to set email alerts
|

LIM and cysteine-rich domains 1 (LMCD1) regulates skeletal muscle hypertrophy, calcium handling, and force

Abstract: BackgroundSkeletal muscle mass and strength are crucial determinants of health. Muscle mass loss is associated with weakness, fatigue, and insulin resistance. In fact, it is predicted that controlling muscle atrophy can reduce morbidity and mortality associated with diseases such as cancer cachexia and sarcopenia.MethodsWe analyzed gene expression data from muscle of mice or human patients with diverse muscle pathologies and identified LMCD1 as a gene strongly associated with skeletal muscle function. We trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Further, in the myocardium of persons with DS, cells were found to be enlarged in comparison to controls (Recalde et al, 1986). Interestingly enough, several studies showed that some proteins codified by genes located in the so-called Down Syndrome Critical Region (DSCR) are involved in the calcineurin-NFAT signaling (Rothermel et al, 2003; Arron et al, 2006; Gwack et al, 2006), which regulates a hypertrophic pathway in myofibers (Dunn et al, 1999; Semsarian et al, 1999; Ferreira et al, 2019) and cardiomyocytes (Molkentin et al, 1998). Such a pathway undergoes destabilization in DS (Arron et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Further, in the myocardium of persons with DS, cells were found to be enlarged in comparison to controls (Recalde et al, 1986). Interestingly enough, several studies showed that some proteins codified by genes located in the so-called Down Syndrome Critical Region (DSCR) are involved in the calcineurin-NFAT signaling (Rothermel et al, 2003; Arron et al, 2006; Gwack et al, 2006), which regulates a hypertrophic pathway in myofibers (Dunn et al, 1999; Semsarian et al, 1999; Ferreira et al, 2019) and cardiomyocytes (Molkentin et al, 1998). Such a pathway undergoes destabilization in DS (Arron et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle comprises approximately 40% of the total body weight. Maintenance of skeletal muscle homeostasis is essential for maintaining the body's various functions (Ferreira et al, 2019;Yamakawa et al, 2020). An imbalance in skeletal muscle homeostasis can cause skeletal muscle hyperplasia or atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…1992; Li et al . 2009; Malabanan and Blind 2016), and transcriptional regulation (Ferreira et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Plexin domain containing 2 gene (Plxdc2) encodes an endothelial cell-surface transmembrane receptor (Cheng et al 2014) that is often co-expressed with Wnt signaling genes (Miller et al 2007). Other candidate hub genes play roles in cell-cell adhesion and differentiation (Wilson et al 2007;Jang et al 2016;Zakaria et al 2019), immune function (Astarita et al 2012;Li et al 2013;Wang et al 2013;Chistiakov et al 2017), nutrient metabolism and delivery (Schmidt et al 1992;Malabanan and Blind 2016), and transcriptional regulation (Ferreira et al 2019).…”
Section: The Evolution Of Placental Gene Expression Networkmentioning
confidence: 99%